Tecnologia de la información comunicaciones y desempeño laboral de los colaboradores de la gerencia comercial de Electro Oriente Iquitos 2024 - Linari Bardales, Wiliam Leonardo (2024)
The study investigated the relationship between the use of Information and Communication Technologies (ICTs) and the job performance of employees in the commercial management of Electro Oriente, Iquitos 2024. Using a descriptive correlational approach and a non-experimental design, it was found a significant and positive relationship between the use of ICTs and job performance, with a Spearman correlation coefficient of 0.788 and a p-value less than 0.01, indicating a strong connection between these variables. This finding confirms the hypothesis and suggests that ICTs positively influence employee job performance. It underscores the importance of effectively implementing and utilizing ICTs in the workplace to enhance productivity and efficiency at Electro Oriente. In conclusion, there is a significant and positive relationship between the use of ICTs and employee job performance, highlighting the importance of investing in technology and training to maximize workforce performance in the company.